Naringin protects memory impairment and mitochondrial oxidative damage against aluminum-induced neurotoxicity in rats. (1st September 2013) - Prakash, Atish; Shur, Bhargabi; Kumar, Anil
<x xml:space="preserve">Abstract</x> Aluminum has been indicated in neurodegenerative disorders and naringin, a bioflavonoid has been used to reduce neurotoxic effects of aluminum against aluminum chloride-induced rats. Therefore, present study has been designed to explore the possible role of naringin against aluminum-induced cognitive dysfunction and oxidative damage in rats. Aluminum (100 mg/kg) and naringin (40 and 80 mg/kg) drug treatment were administered orally for six weeks to male wistar rats. Various behavioral performance tasks, biochemical, mitochondrial oxidative parameters, and aluminum concentration in the brain were assessed. Aluminum chloride treatment significantly caused cognitive dysfunction and mitochondria oxidative damage as compared to vehicle treated control group. Besides, aluminum chloride treatment significantly increased acetyl cholinesterase activity and aluminum concentration in the brain as compared to sham. Chronic administration of naringin significantly improved cognitive performance and attenuated mitochondria oxidative damage, acetyl cholinesterase activity, and aluminum concentration in aluminum-treated rats as compared to control rats. Results of the study demonstrate neuroprotective potential of naringin against aluminum chloride-induced cognitive dysfunction and mitochondrial oxidative damage.